ANALISIS PELAYANAN DI MAL PELAYANAN PUBLIK TERHADAP PEMBERDAYAAN MASYARAKAT MELALUI USAHA MIKRO, KECIL DAN MENENGAH (UMKM) KERAJINAN KERANJANG DI DESA GAPURA TIMUR KABUPATEN SUMENEP - Iffah Nurlaily; Endang Widyastuti (Journal MISSY (Management and Business Strategy), 2020)
Empowerment is a way, a process, an act of empowering. So that community empowerment can be interpreted that the way society processes. In this case, the community proceeds in the UMKM. The process referred to here is a process to improve the economic situation of surrounding communities that is unstable. This research uses a qualitative approach with a descriptive method. This research is located in the East Gapura Village, Sumenep Regency. Data collection techniques used through interviews, observation and documentation. This research will explain how community empowerment through UKM Craft Basket in the East Gapura Village, Sumenep Regency. The results obtained from this study indicate that the process of community empowerment through MSME Basket Craft is going well. The factor that encourages the running of this UMKM well is that there is only 1 UMKM in the East Gapura Village, Sumenep Regency. While the inhibiting factor is the limited material used to make basket crafts not yet available in the nearest area.